Unveiling the behavioral nexus of innovative organizational culture: identification and affective commitment of teachers in primary schools - Al-Shuhumi, Said Rashid Ali Rashid; Al-Hidabi, Dawood Abdulmalek Yahya; Al-Refaei, Abd Al-Aziz (Taylor & Francis Group, LLC, 2023)
A rigorous revision of the current body of literature is required to obtain an accurate assessment of the impact of innovative organizational culture on teachers’ identification and affective commitment in primary school environments. The current literature requires more investigation into the mediating function of teachers’ identification in the relationship between innovative culture and teachers’ affective commitment. This underscores the necessity for a more comprehensive comprehension of this mediating mechanism. Therefore, through combining two theoretical frameworks, Behavioral Commitment Theory (BCT) and Social Identity Theory (SIT), this study delves into the intricate psychological interplay between innovative organizational culture and its influence on teachers’ sense of identification and affective commitment in primary schools, which could provide insight into more understanding of this phenomenon. By surveying 432 teachers, this study sought to discern the direct impacts of an innovation-driven culture on teachers’ organizational identification and affective commitment and the potential mediating role of this identification. The findings of this study, which were inferred from the Structural Equation Modeling (SEM), illuminate that an innovative atmosphere significantly resonates with teachers’ identification and affective commitment. Additionally, this identification emerges as a bridge that further intensifies teachers’ emotional bond (affective commitment) with their institution in the context of innovation culture. This research contributes valuable insights for educational institutions and provides practical implications for students, teachers, and schools, while highlighting certain constraints and avenues for future exploration